Clinical management of alemtuzumab-induced autoimmune thyroid diseases: a narrative review - Jacopo Manso; Ilaria Muller; Caterina Mian (European Thyroid Journal)
Alemtuzumab is a powerful anti-CD52 drug that is an established treatment option in patients with multiple sclerosis due to its proven efficacy. However, in about 50% of patients, the use of alemtuzumab is burdened by the development of secondary autoimmune thyroid diseases, constituting a range of alemtuzumab-induced autoimmune thyroid diseases (AIATDs). Graves' disease (GD) is the most common AIATD, with an incidence of approximately 60%, and presents different characteristics from the conventional form. Indeed, GD with a fluctuating course is significantly more prevalent (15–50%), which poses a major challenge for physicians in its management. Other AIATDs also exhibit distinct features compared to their conventional counterparts; notably, hypothyroidism is frequently associated with TSH-receptor blocking antibodies, and alemtuzumab-induced GD demonstrates a higher rate of fluctuating course and potential for spontaneous remission. Alemtuzumab-induced thyroid eye disease (TED) is less common than conventional TED, with similar clinical and management characteristics. In this review, we summarize the latest evidence, also from real-world studies, with a focus on clinical management and possible predictors of AIATDs.